Experimental Study of the Performance of Base Metal and Welding Line of the Household LPG Cylinder Manufactured in Kurdistan Region (International Journal of Engineering Materials and Manufacture, 2020)
Liquefied petroleum gas (propane or butane) is a colourless liquid which readily evaporates into a gas. It has no smell, although it will normally have an odour added to help detect leaks. Liquefied petroleum gas is stored and handled as a liquid when under pressure inside an LPG cylinder. Liquefied petroleum gas cylinders are subjected to various tests to ensure their compliance requirements as per standard. This research studied the durability of welding and performance of base metal of LPG home cylindrical in Kurdistan region. The experiments were carried out on an unformed plate and three types of LPG cylinder designated as A, B, and C and D. In this research standard tests for LPG cylinders were conducted. Three samples were extracted from each of LPG cylinders and unformed plate for each of tensile test, bending test and hardness test according to ISO 6892-2016 and ASME standards to examine the mechanical properties. In addition, chemical compositions also were carried out. These values are compared with standard.